Adsorptive removal of tetracycline from aqueous solution by maple leaf-derived biochar. (June 2020) - Kim, Ji Eun; Bhatia, Shashi Kant; Song, Hak Jin; Yoo, Eunjin; Jeon, Hyeon Jin; Yoon, Jae-Yoon; Yang, Yunjeong; Gurav, Ranjit; Yang, Yung-Hun; Kim, Hyung Joo; Choi, Yong-Keun
Graphical abstract: Highlights: Maple leaf-derived biochars were prepared at the different pyrolytic temperature. Biochar produced at 750 °C showed BET surface area of 191.1 m 2 /g. Selected biochar presented maximum adsorption capacity of 361 mg/g. Adsorption of tetracycline followed pseudo-second-order and Freundlich models. Abstract: The present study evaluates the physicochemical properties of maple leaf-derived biochars (M-BCs) produced at different pyrolytic temperatures (i.e., 350, 550, and 750 °C) and their adsorptive properties for tetracycline onto M-BCs. The increase in pyrolysis temperature to produce M-BCs led to a significant increase in the biochar's hydrophobicity, surface area, and calcite (CaCO3 ) crystallization. The M-BC750 produced without functionalization or activation possessed a high calcite composition and a hydrophobic nature with lower O/C and H/C, hydroxyl groups (–OH) on the surface, and functional groups (i.e., O-containing) as H-bond acceptors. Among M-BCs, the M-BC750 present a highest TC adsorption capacity owing to possible mechanisms such as metal complexation, H-bonding, and hydrophobic interactions. The isotherm and kinetic models for TC adsorption followed the Freundlich models and pseudo-second-order models, respectively. M-BCs produced from the waste fallen maple leaves could be applied as low-cost environmental adsorbents for TC removal.